Morphometrics and reproduction of Terebrasabella heterouncinata (Polychaeta:Sabellidae), infesting abalone (Haliotis midae) from different culture environments - Gray, Michael (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2003)
In the late 1980's abalone culturalists noticed reduced growth rate and shell deformities in some abalone stocks. These problems were the result of infestations by a shell boring polychaete, Terebrasabella heterouncinata. Under intensive abalone culture conditions the level of infestation can reach epidemic proportions and there are often severe consequences for the host abalone. Heavy sabellid infestation levels have placed the economic viability of several South African farms under threat. This study formed part of an ongoing project that is aimed at investigating the basic biology of Terebrasabella heterouncinata. The majority of abalone farmers in South Africa feed their abalone either naturally occurring kelp (Ecklonia maxima) or the formulated abalone feed, Abfeed. Farmers have suggested that the use of Abfeed is associated with higher sabellid infestation levels and changing the abalone diet from Abfeed to kelp helps reduce sabellid infestation. Speculation has arisen indicating that older, slower growing abalone are more susceptible to sabellid infestation. The effect of host abalone diet history and their growth on sabellid settlement success, morphometries and reproduction was quantified. To better understand the plasticity of the expression of life history traits the variability of morphometric and reproductive characteristics was compared between different farm environments. And more...
Keywords: Polychaeta; Sabellidae; Abalones -- Physiology; Abalones -- Nutrition; Abalone culture